WANITA SEBAGAI KELOMPOK MASYARAKAT RENTAN (Gambaran Kehidupan Wanita Iran dalam Novel Banat Iran Karya Nahid Rachlin) - Hamdan (MUWAZAH : jurnal kajian gender, 2013)
This research was conducted to reveal in depth some issues related suppression of Iranian women in the pre-revolution 1979 in the novel Banat Iran by Nahid Rachlin (2008). It was interesting to discuss because the issue of the oppression of Iranian women has not been known. The Banat Iran novel presented the oppression of Iranian women and this novel can be analyzed with the review of feminist literary criticism.